2004
DOI: 10.1021/ac0493875
|View full text |Cite
|
Sign up to set email alerts
|

Differential Mass Spectrometry:  A Label-Free LC−MS Method for Finding Significant Differences in Complex Peptide and Protein Mixtures

Abstract: Efficiently identifying and quantifying disease- or treatment-related changes in the abundance of proteins is an important area of research for the pharmaceutical industry. Here we describe an automated, label-free method for finding differences in complex mixtures using complete LC-MS data sets, rather than subsets of extracted peaks or features. The method selectively finds statistically significant differences in the intensity of both high-abundance and low-abundance ions, accounting for the variability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
220
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 260 publications
(221 citation statements)
references
References 29 publications
0
220
0
1
Order By: Relevance
“…In the first group, spectral features (typically isotopic clusters indicating a peptide) are detected first and then statistically compared [25][26][27][28][29]. Alternatively, the second group applies statistics first so that only differential features are detected from the extracted ion chromatograms [30][31][32][33]. Both computational methods rely on the ability to chromatographically align multiple LC-MS runs from different samples, identify differences between the samples and determine the magnitude of the change ( Figure 5).…”
Section: Differential Ms Quantitationmentioning
confidence: 99%
“…In the first group, spectral features (typically isotopic clusters indicating a peptide) are detected first and then statistically compared [25][26][27][28][29]. Alternatively, the second group applies statistics first so that only differential features are detected from the extracted ion chromatograms [30][31][32][33]. Both computational methods rely on the ability to chromatographically align multiple LC-MS runs from different samples, identify differences between the samples and determine the magnitude of the change ( Figure 5).…”
Section: Differential Ms Quantitationmentioning
confidence: 99%
“…Differential mass spectrometry was performed as previously© reported© [14].© Measured© (time,© m/z,© intensity) points were regularized onto a standard (time, m/z) grid,© with© spacing© of 3 s in time© and© 0.01© m/z units© [14]. A t-test was performed to produce a single p value describing the extent to which mean intensities differ between the two conditions at each elution time and m/z.…”
Section: Dms Analysis and Ratio Determinationmentioning
confidence: 99%
“…Had we compared data from an individual LC-MS acquisition for each condition (Mixture A and Mixture B) and used a subtraction method to look for differences in abundance, almost all of the observed ion species would have been found to have different abundances. The majority of these differences could be considered false positives because they arise due to variability in peak intensity measurements rather than from the differentially-spiked©peptides©in©this©experiment.©dMS© [14] minimizes these false positives because it considers only peptide changes that are statistically significant between two or more conditions. In other experiments, biological variability among different subjects as well as technical variability in sample preparation and MS measurement must be taken into consideration in the statistical analysis of the MS signals.…”
Section: Reproducible Lc-ftms Analysis Of Complex Peptide Mixturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it was shown that ICAT was an excellent tool for discovery of proteases making it useful in degradomic research [37]. Recently, a new version of the ICAT method was investigated [38]. The advantage of this new strategy is the use of 13 C as the heavy version and 12 C as the light version to eliminate the slight delay in retention time of peptides treated with the light tag that occurs with hydrogen and deuterium.…”
Section: "Labeled" and "Label-free" Technologiesmentioning
confidence: 99%